2022
DOI: 10.17583/qre.10474
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Online Learning across Cultures: the Role of Teaching and Social Presence

Abstract: Collaborative online learning (COL) has been associated with positive outcomes, such as critical thinking, shared problem-solving skills, and deep learning. Such outcomes require pedagogies that consider students’ backgrounds, including the cultural context in which they operate. This study reflects upon the role of culture through the lens of the Community of Inquiry Framework (CoI) and the elements of social - and teaching presence. German and Thai students were selected due to cultural differences in values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…They also highlighted the opportunity to work in a more dynamic and creative way, which allowed them to develop relevant skills for their academic and professional development. These results corroborate the importance of providing meaningful learning experiences with online resources which are transferable to the professional context [1,31].…”
Section: Discussionsupporting
confidence: 78%
“…They also highlighted the opportunity to work in a more dynamic and creative way, which allowed them to develop relevant skills for their academic and professional development. These results corroborate the importance of providing meaningful learning experiences with online resources which are transferable to the professional context [1,31].…”
Section: Discussionsupporting
confidence: 78%
“…Counter to research on the personalization principle arguing that the talking head helps maintain appropriate levels of attention (Kizilcec et al, 2015) and research showing that including a video would make participants feel most connected (e.g., Cui et al, 2013; Grothaus, 2022; Ritonga et al, 2022), we found that participants in the audio-only video gave the highest ratings for social connectedness compared to the conditions that either featured a video display of the speaker at the beginning and end of the video or the picture overlay of the speaker throughout the learning video. Thus, our findings expand on previous research suggesting that the benefit of including a PiP overlay may depend on how familiar the audience is with the presenter.…”
Section: Discussionmentioning
confidence: 99%
“…The data that has been processed is then drawn to conclusions. Conclusions are the process of extracting the essence of data that has been organized in the form of short and concise sentence statements but containing broad meaning (Grothaus, 2022).…”
Section: Methodsmentioning
confidence: 99%